2021
DOI: 10.1108/ci-05-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

Tracking major resources for automated progress monitoring of construction activities: masonry work case

Abstract: Purpose The purpose of this study is to monitor the progress of construction activities in an automated way by using sensor-based technologies for tracking multiple resources that are used in building construction. Design/methodology/approach An automated on-site progress monitoring approach was proposed and a proof-of-concept prototype was developed, followed by a field experimentation study at a high-rise building construction site. The developed approach was used to integrate sensor data collected from mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…On the other hand, Kaasinena [52] notes that the night shift was less hectic than other shifts and that this was because the lighter work tended to be scheduled at night. The findings of this study are also consistent with findings from other industries such as construction [53], agriculture [54], and healthcare [55], all of which are difficult to automate to reduce night work. Folkard and Tucker [39] advocated the abandonment of night work and suggested that all the advantages and disadvantages of this form of work should be examined.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Kaasinena [52] notes that the night shift was less hectic than other shifts and that this was because the lighter work tended to be scheduled at night. The findings of this study are also consistent with findings from other industries such as construction [53], agriculture [54], and healthcare [55], all of which are difficult to automate to reduce night work. Folkard and Tucker [39] advocated the abandonment of night work and suggested that all the advantages and disadvantages of this form of work should be examined.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, data collected through OBI are not useful for tracking productivity [1]. Therefore, to make it more effective, it must be combined with information regarding the material quality and site environment, as presented in [48]. It is very difficult to avoid accidents involving other cranes and building structures, as well as swaying loads, when it comes to workplace safety [21].…”
Section: Data Collection A) Onboard Instrumentation System (Obis)mentioning
confidence: 99%
“…By using this simpler kind of information, the progress estimation can be based on an interpretation of localization data via in-area analysis. Guven and Ergen (2020) have used RFID to track major construction equipment and resources (e.g. Tower Crane), which is fused with the crane load sensor, and afterward analyzed in a rule-based reasoning system (Pradhan and Akinci, 2012).…”
Section: Location-based Approachesmentioning
confidence: 99%
“…Tower Crane), which is fused with the crane load sensor, and afterward analyzed in a rule-based reasoning system (Pradhan and Akinci, 2012). However, resource tracking has a significant drawback as the construction material must be tagged to follow it through delivery, movement and application (Guven and Ergen, 2020).…”
Section: Location-based Approachesmentioning
confidence: 99%